If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(q + -2) = 3(9 + -12) Reorder the terms: 9(-2 + q) = 3(9 + -12) (-2 * 9 + q * 9) = 3(9 + -12) (-18 + 9q) = 3(9 + -12) Combine like terms: 9 + -12 = -3 -18 + 9q = 3(-3) Multiply 3 * -3 -18 + 9q = -9 Solving -18 + 9q = -9 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 9q = -9 + 18 Combine like terms: -18 + 18 = 0 0 + 9q = -9 + 18 9q = -9 + 18 Combine like terms: -9 + 18 = 9 9q = 9 Divide each side by '9'. q = 1 Simplifying q = 1
| 10-8x=125-43x | | 300-12x=400-17x | | 5(x-3)-2(x-3)-9=0 | | 3x+(x-1)+(3x+1)=56 | | -16(3-29)=432 | | 3x^4*x-10=0 | | (x-6)(3x-2)=(x-16)(2x+1) | | 2x-1=7-4x | | (2x+1)(x-16)=(3x-2)(x+3) | | 0.36p+0.26=3.36 | | 0.4(0.1x+.3)=-0.8 | | 2x^2-10x-3=0 | | (-5x/7)-8=-9 | | (-5x/7)-8=9 | | 1/5(5x-5)=4 | | 2-6-(3-x)=21-7x | | y=(2-5k)x | | 5b+2=2b+7 | | 7x-1.8=3x+1.4 | | 2b=3b | | 4*(x+5)+8=4x | | 2*(x+3)+4*(x-5)=-14 | | 2(x+3)+4(x-5)=-14 | | x-1.4=0 | | 5x+6=5x+45 | | 5x+6=5x+31 | | -15x+2x=-11 | | 14x-6x^2+3=0 | | 14x(-43)+7=83 | | 14x+4=5x+13 | | 3w-1+3(2w+1)=-5(w+2) | | 5(x-6)-5=-7(-2x+7)-5x |